2017
DOI: 10.1016/j.enpol.2017.02.053
|View full text |Cite
|
Sign up to set email alerts
|

The merit order effect of Czech photovoltaic plants

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…The Czech Republic is one of the most industrialized economies and developed in the Central and Eastern Europe. The Czech electricity market is characterized by a very positive attitude towards nuclear power, a dominant position of lignite in the Czech Republic electricity generation, and a strong role of electricity export since the Czech Republic ranks sixth in the world and fourth in Europe in electricity exports [33]. The dominant source of energy in the Czech Republic is solids (hard coal and lignite), which constitutes 39% of the total primary energy supply.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Czech Republic is one of the most industrialized economies and developed in the Central and Eastern Europe. The Czech electricity market is characterized by a very positive attitude towards nuclear power, a dominant position of lignite in the Czech Republic electricity generation, and a strong role of electricity export since the Czech Republic ranks sixth in the world and fourth in Europe in electricity exports [33]. The dominant source of energy in the Czech Republic is solids (hard coal and lignite), which constitutes 39% of the total primary energy supply.…”
Section: Methodsmentioning
confidence: 99%
“…Before legislation reacted to the photovoltaic boom (by the end of 2010), the Czech installed solar capacity rose from 40 MW in 2008 to 1960 MW in 2010. The Czech subsidy for solar electricity dropped from an initial 15,565 Czech crowns (CZK)/MWh in 2006 to zero for newly built commercial photovoltaic plants in 2014 [33].…”
Section: Methodsmentioning
confidence: 99%
“…Havlíčková et al (2011) a Blahová et al (2014 se zaměřují na využití biomasy v české energetice. Českou solární energetikou se podrobně zabývají Sokol et al (2011), Průša et al (2013) a Luňáčková et al (2017. Náš článek se snaží tuto mezeru v literatuře vyplnit.…”
Section: úVodunclassified
“…The methods for the examination of MOE are based on two main approaches [1,2], which are as follows: (a) the development of electricity market models, which simulate the operation of DAM and calculate the resulted spot electricity price for various scenarios [3][4][5][6][7][8][9] and (b) the regression analysis approach, which uses historical price and generation data in order to quantify the actual achieved reduction in spot price for a given period of time [2,3,[10][11][12][13][14]. Studies that combine both approaches are also met [15].…”
Section: Introductionmentioning
confidence: 99%
“…The significant impact of wind generation on spot prices was also proven by Jónsson et al [11], who used a non-parametric regression model to analyze the Danish electricity market. Similarly, based on the regression approach, Luňáčková et al [14] quantified the MOE in the Czech market by using six years of hourly, daily, and weekly data (2010-2015), which led to the outcome of a 10% increase in RES deployment, except from solar which had a negative impact in general, and caused a 2.5% decrease in electricity price. Gelabert et al [10] used a multivariate regression model to estimate the MOE of the RES and cogeneration in Spain between 2005 and 2010 and showed that a marginal increase of 1 GWh of electricity production from the previous technologies leads to a decrease of 2€/MWh in electricity prices.…”
Section: Introductionmentioning
confidence: 99%